Preparation of Administrative Boundary Map of Arahan Kidul Village, Arahan District , Indramayu Regency, West Java - Nurul Aulia Dewi (Journal of Social Science)
This research aims to create a map of village administrative boundaries in the Arahan Kidul area using GIS software. By combining data from various sources and utilizing the analysis features provided by GIS, this research aims to complete incomplete village data and produce administrative boundary maps that are accurate and informative. It is hoped that the results of this research can contribute to regional management, development planning and preventing conflicts related to village boundaries.